Email classification and meeting scheduling using classifier algorithm - Khan, Behroz Newaz; Saroar, Sk Golam; Alam, Md. Mosfaiul; Gomes, Sebastian Romy (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.